Assessing the Rate of Child Maintenance (Financial Support) from a Shariah Perspective: the Case of Malaysia - Bahiyah Ahmad; Raihanah Hj. Azahari; Asmak Ab Rahman; Mazni Abdul Wahab (Al-Jami'ah Research Centre, 2020)
Shariah mandates the criteria of kifāyah and ma’rūf in assessing maintenance for wives and children; however, these criteria currently require assesment and evaluation as maintenance is mostly influenced by society’s practices and by socioeconomic status. Consequently, Malaysia’s Islamic Family Law (Federal Territory) Act 1984 presribes that the maintenance assesment for wives and children must be based on the means (ma’rūf) and needs (kifāyah) of the parties. However, this provision is too general and there is no clear explanation of what constitutes these criteria for the parties. This provision has troubled some parties as it leaves the determination of the maintenance rate to a judge’s discretion regarding both criteria. This study, with a methodology of content analysis and in-depth interviews, determines an assessment formula for both criteria in assessing child maintenance. Hukum Islam mensyaratkan dua kriteria dalam pemberian nafkah istri dan anak yaitu kifāyah dan ma’rūf. Namun kriteria tersebut saat ini perlu ditinjau dan evaluasi lagi sesuai dengan praktik masyarakat serta keadaan social ekonomi saat ini. Seperti yang terdapat dalam hukum perundangan keluarga Islam Malaysia tahun 1984 yang menyatakan bahwa ma’rūf dan kifāyah menjadi syarat utama pemberian nafkah istri dan anak. Bagaimanapun penjelasan kriteria tersebut masih terlalu umum dan kurang jelas. Hal ini juga menyisakan beberapa persoalan akibat keputusan pengadilan yang mendasarkan pada kedua kriteria tersebut. Dengan menggunakan pendekatan analisis isi dan wawancara mendalam, kajian ini menguatkan penilaian kedua kriteria tersebut.